Correlation Between Standardized Uptake Value in Preneoadjuvant and Postneoadjuvant Chemoradiotherapy and Tumor Regression Grade in Patients With Locally Advanced Esophageal Cancer. (March 2018) - Baksh, Kathryn; Prithviraj, Gopi; Kim, Youngchul; Hoffe, Sarah; Shridhar, Ravi; Coppola, Domenico; Centeno, Barbara; Pimiento, Jose; Meredith, Kenneth; Almhanna, Khaldoun
Abstract : Purpose: To investigate whether positron emission tomography/computed tomography (PET/CT) initial and restaging imaging predicts for pathologic response measured by tumor regression grade (TRG) after preoperative chemoradiotherapy (CRT) in patients with locally advanced esophageal cancer. Methods: A retrospective review of 220 patients with stage II-III esophageal cancer treated with neoadjuvant CRT followed by surgery was performed. In total, 187 patients were eligible for statistical analysis. Pretreatment and posttreatment PET/CT scans were reviewed. Maximum standard uptake value (SUV) at the site of the primary tumor was recorded before and 6 weeks after neoadjuvant therapy. Upon completion of surgery, TRG was determined by a specialized site-specific gastrointestinal pathologist. Spearman correlation was used to compare pre, post, and change in maximum SUV, TRG, and overall survival. Results: The median follow-up was 24 months. Although no significant correlation was found between pretreatment SUV and TRG ( r =0.073, P =0.32), post-CRT SUV, however, showed a significant positive correlation with TRG ( r =0.374, P <0.01). There was no significant correlation between the absolute change in fluorodeoxyglucose uptake after CRT and TRG ( r =0.057, P =0.44); however, the rate of SUV change showed a significant correlation with TRG ( r =0.178, P =0.017). Similar to previous studies, our study showed a significant difference in overall survival between TRG groups (log-rank test, P =0.019). Patients with TRG 3 showed prominently worse survival with median survival of 27.4 months. Patients with favorable pathologic responses were those whose scans demonstrated a metabolic response defined as a decrease in SUV≥70%. Conclusions: Changes in SUV uptake on PET/CT scans after CRT have prognostic value in predicting pathologic response of esophageal cancer after neoadjuvant therapy. Further studies are needed to validate the integration of PET/CT as a decision-making tool. Abstract : Supplemental Digital Content is available in the text.